Does the Islamic Banks Lending Structure Matter? - Abdul Rahman, A.; Haji Ibrahim, M.; Mydin Meera, A. K. (Universiti Sains Islam Malaysia, 2024)
This study investigate the impact of lending structure on the Islamic banks insolvency risk exposure by analysing four lending structure instrument 1) the ratio of real estate lending to total asset; 2) lending concentration; 3)short term lending portfolio stability; and 4) medium term lending portfolio stability. Our findings indicate that an increase in real estate lending could decrease the Islamic banks insolvency risk exposure. Similarly, our result for lending concentration show that loan specialisation could reduce islamic banks insolvency risk exposure. Hence, policy makers as well as practitioners lay react accordingly to this finding.